Habitat amount modulates the effect of patch isolation on host-parasitoid interactions - Coudrain, Valérie; Schüepp, Christof; Herzog, Felix; Albrecht, Matthias; Entling, Martin H. (Frontiers in Environmental Science, 2014)
Habitat amount and patch isolation are important determinants of biodiversity and ecosystem functioning. We studied the separate and interactive effects of these two components of habitat fragmentation on host-parasitoid interactions in a replicated landscape-scale study. We used trap-nesting solitary bees, wasps and their natural enemies as study system. We exposed trap nests in 30 tree patches in agricultural landscapes in northern Switzerland. Study sites were either (i) adjacent to forest (adjacent), (ii) distant from forest but connected through woody elements (connected) or (iii) distant from forest with no connecting woody elements (isolated). Independent of the three levels of isolation, the amount of woody habitat in the landscapes covered a gradient from 4 to 74%.Host and parasitoid species richness increased with the amount of habitat in the landscape and was strongly reduced at isolated compared to adjacent and connected sites. Loss of host species richness was 21% at isolated compared to non-isolated sites, whereas parasitoid species richness decreased by 68%, indicating that the higher trophic level was more adversely affected by isolation. Most importantly, habitat amount and isolation had a pronounced interactive effect on parasitism: while isolation resulted in a strong decrease in parasitism in landscapes with low habitat amount, this effect was mitigated by high habitat amount. These interactive effects were consistent across the three years of the study. The observed interplay between habitat amount and patch isolation may explain the often conflicting results in the habitat fragmentation literature and should be considered in future research on multitrophic communities and ecosystem functioning in fragmented landscapes.